Determinants of Gross Regional Domestic Product (GRDP) in Berau Regency - Puspitasari, Lisa (Perpustakaan dan Penerbitan Unismuh Makassar, 2025)
This study aims to analyze the influence of the Human Development Index (HDI) and population size on the Gross Regional Domestic Product (GRDP) in Berau Regency. Economic growth, as reflected by GRDP, serves as a key indicator of regional development and is shaped by both human capital and demographic dynamics. HDI includes essential components such as education, health, and standard of living, which collectively reflect the quality of human resources. Meanwhile, population size is closely related to labor availability and consumption potential, both of which contribute to regional economic performance. This research utilizes secondary data sourced from the Central Bureau of Statistics (BPS) of Berau Regency covering the period from 2016 to 2022. Multiple linear regression analysis is employed to assess the relationship between the variables. The results reveal that the F-calculated value (14.578) exceeds the F-table value (6.94), indicating that HDI and population size simultaneously have a statistically significant effect on GRDP. Additionally, the significance value of 0.015—being less than the 0.05 threshold—confirms that both variables positively and significantly influence regional economic output. Based on these findings, it is recommended that local government authorities formulate strategic development policies that focus on enhancing the Human Development Index and maximizing the economic benefits of population growth to promote sustainable development. However, this study is limited by the use of only two independent variables and data confined to a single region and time frame, which may restrict the generalizability of the findings. Future research should consider incorporating additional variables, such as labor force participation, investment, or technological advancement, and expanding the geographical scope to provide more comprehensive insights.